Determinan Kejadian Stunting pada Balita - Wardita, Yulia; Suprayitno, Emdat; Kurniyati, Eka Meiri (Fakultas Ilmu Kesehatan, 2021)
Determinant of stunting incident in Saronggi Subdistrict, Sumenep Regency. The prevalence of stunting of toddlers in East Java is higher than the average prevalence at the national level of 32.8%. In 2020, the Health Office of East Java Province mentioned that the prevalence of stunting in SumenepRegency reached 170 toddlers spread across 14 villages. The highest prevalence of stunting was found in NongGunongSubdistrict which reached 6.02% and in SaronggiSubdistrict which reached 4.05%.This study aims to analyze the influence of maternal pregnancy history, nutritional status of children, parenting patterns, maternal knowledge and history of exclusive breastfeeding to stunting.This research is analytical research with case-control design. The samples used were 30 mothers with toddler cases and 30 mothers with control toddlers.Maternal pregnancy history, child nutrition status, parenting patterns, maternal knowledge and exclusive breastfeeding have a significant influence on stunting incidents in Saronggi Subdistrict, Sumenep Regency.Mothers must meet the intake of good nutrition, provide exclusive breastfeeding and good parenting patterns and health officials must improve health education programs, especially about stunting so that maternal knowledge can be improved and stunting problems can be addressed immediately.